Use of dielectrophoresis for directing T cells to microwells before nanostraw transfection: modelling and experiments. Issue 47 (24th October 2022) - Lard, Mercy; Ho, Bao D.; Beech, Jason P.; Tegenfeldt, Jonas O.; Prinz, Christelle N.
Abstract : Dielectrophoresis can be used to guide cells to microwells with nanostraws at the bottom. This ensures a high nanostraw occupancy, minimizing the current leak through unoccupied nanostraws while maintaining a high cell viability, even if the total number of cells is low. Abstract : Nanostraw substrates have great potential for achieving minimally invasive cell transfection. Cells located on the nanostraw substrate are subjected to mild DC electric pulses applied across the nanostraw substrate, which open pores in the cell membrane on top of the nanostraws and drives charged cargo through these pores via electrophoresis. However, with this method, the current may leak through uncovered nanostraws, thereby decreasing the desired effect in the cell-covered nanostraws. A minimization of the number of uncovered nanostraws could be achieved by high cell coverage, but this is challenging when working with small cell populations. Nanostraw substrates of smaller area could be covered by smaller cell populations but are hard to integrate into fluidics systems. Here, we use simulations and experiments to show that this issue can be addressed by covering the nanostraw substrate with an insulating layer containing pores of similar size to cells. The pores act as traps into which cells can be guided using dielectrophoresis, ensuring a high degree of occupancy while maintaining a high cell viability, even if the total number of cells is low.